Pemanfaatan Tanaman Hasil Rekayasa Genetik: Status, Regulasi, dan Metode Deteksi di Indonesia - Bahagiawati Bahagiawati; Sutrisno Sutrisno (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2007)
Application of Genetically Modified Crops: Status, Regulation,and Detection Method in Indonesia. Bahagiawatiand Sutrisno. Global area of transgenic crop was increasetremendously. The number of country accepting of plantingand/or marketing the transgenic crops and its derivativeproducts also become more numberous. However, due toexisting controversy on the benefit and risk, the applicationof transgenic crops was governed by regulations to protectthe consumer and environment from its unwanted effects.There are some international conventions that managingand controlling the uses of these crops, one of them wasCartagena protocol that Indonesia ratified in 2004. Indonesiaalso launched a regulation upon labelling package foodderived from transgenic crops in 1999. To implement eitherthe Cartagena protocol and labelling regulation, Indonesianeeds to increase its capacity to detect the present of thetransgenic crop product either in raw, and proceesed food.This review will discuss about the development of theapplication of transgenic crop and its product globally, andlist of transgenic crops that have been accepted andapproved as safe for human consumption and environment.The regulations upon the application of transgenic crop inIndonesia also be informed. Some metodologies to detectthe presence of the genetically modified food that aregenerally use in some countries also be discussed in thisreview.